“Bring security to the people and not the people to security”: security, refugee, and ethnic minority policies and implementation in Vietnam’s central highlands, 1968-1975 - Cohen, Matthew F. (Kansas State University, 2011)
The central highlands of Vietnam were of vital strategic importance during the Second Indochina War (1955-1975); the collapse of South Vietnamese forces in this region in March 1975 led to the fall of Saigon just one month later. Despite this area’s importance, most central highlands historiography addresses large military campaigns, such as the 1972 Nguyen Hue “Easter Offensive” and the 1975 Ho Chi Minh Offensive. Micro-histories are of great value in examining the implementation of national programs, yet all province case studies examine events in the more heavily populated and ethnically homogeneous Saigon and Mekong Delta regions of the Republic of Vietnam (RVN). This thesis examines Lam Dong province, at the southern end of the Vietnamese central highlands. Focusing on the territorial forces initiative and RVN policy toward ethnic minority Montagnards in the highlands—two vital yet under-studied topics in Vietnam War historiography—this study demonstrates the operational success of the former and the strategic failure of the latter. The thesis is organized chronologically and concentrates on the final six years of the war, when South Vietnamese officials were increasingly promulgating and executing policy. The first part of the study details background information and outlines the war through 1967, when the National Liberation Front (NLF) held the advantage. The middle section scrutinizes the late 1960s and early 1970s and describes the factors that led to increased province security. The final section analyzes the final two years of the war following the departure of U.S. troops. In this period, South Vietnamese forces held the advantage against a weakened NLF, yet ordinary citizens’ discontent reached a climax. In-depth study of both province- and national-level documents from this period demonstrates that local officials, both American and Vietnamese, often attempted to address challenges but were hindered by the centralized nature of the Saigon bureaucracy. The inability and unwillingness of the RVN to address adequately issues such as highlands refugee policy led to the gradual dissatisfaction of many Montagnards in the highlands. This study elucidates RVN initiatives such as the territorial force, Main Living Area, and Return to Village programs—seldom-mentioned yet key facets of the Saigon government’s attempt to mollify ethnic tensions and counter the threat posed by the NLF.
Keywords: Central highlands; Montagnards; Lam Dong; Regional forces; Popular forces; Republic of Vietnam Armed Forces; History (0578)